A conceptual framework for interprofessional shared decision making in home care: Protocol for a feasibility study - Légaré, France; Stacey, Dawn; Brière, Nathalie; Desroches, Sophie; Dumont, Serge; Fraser, Kimberley; Murray, Mary-Anne; Sales, Anne; Aubé, Denise (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Shared decision making (SDM) is fundamental to informed consent and client-centered care. So far, SDM frameworks have been limited to the client-physician dyad, even though care is increasingly delivered by interprofessional (IP) teams. IP collaboration is especially essential in home care, one of health care's most rapidly growing areas. This study will assess whether it is possible to practice SDM in IP home care. Methods/Design We will use a qualitative case study and a quantitative survey to capture the macro, meso and micro levels of stakeholders in home care. The case study will follow the knowledge-to-action process framework to evaluate the work of an IP home care team at a Quebec City health center. Sources of data will include one-on-one interviews with patients, family caregivers or surrogates and significant others, and administrators; a focus group of home care health professionals; organizational documents; and government policies and standards. The interview guide for the interviews and the focus group will explore current practices and clinical problems addressed in home care; factors that could influence the implementation of the proposed IP approach to SDM; the face and content validity of the approach; and interventions to facilitate the implementation and evaluation of the approach. The survey will ask 300 health professionals working in home care at the health center to complete a questionnaire based on the Theory of Planned Behaviour that measures their intentions to engage in an IP approach to SDM. We will use our analysis of the individual interviews, the focus group and the survey to elaborate a toolkit for implementing an IP approach to SDM in home care. Finally, we will conduct a pilot study in Alberta to assess the transferability of our findings. Discussion We believe that developing tools to implement IP SDM in home care is essential to strengthening Canada's healthcare system and furthering patient-centered care. This study will contribute to the evaluation of IP SDM delivery models in home care. It will also generate practical, policy-oriented knowledge regarding the barriers and facilitators likely to influence the practice of IP SDM in home care.